Aspergillus flavus: A potential Bioremediator for oil contaminated soils - Maruthi, Y.Avasn; Hossain, Kaizar; Thakre, Sujata (European Journal of Sustainable Development, 2013)
Biodegradation is cost-effective, environmentally friendly treatment for oily contaminated sites by the use of microorganisms. In this study, laboratory experiments were conducted to establish the performance of fungal isolates in degradation of organic compounds contained in soils contaminated with petrol and diesel. As a result of the laboratory screening, two natural fungal strains capable of degrading total organic carbons (TOC) were prepared from isolates enriched from the oil contaminated sites. Experiments were conducted in Erlenmeyer flasks under aerobic conditions, with TOC removal percentage varied from 0.7 to 32% depending on strains type and concentration. Strains Phanerocheate chrysosporium and Aspergillus niger exhibited the highest TOC removal percentage of 32 and 21%, respectively, before nutrient addition. TOC removal rate was enhanced after addition of nutrients to incubated flasks. The highest TOC reduction (45%) was estimated after addition of combination of nitrogen, phosphorus and sulphur to Phanerocheate chrysosporium strains. Results of experimental work carried out elucidate that the fungi like Phanerocheate chrysosporium and Aspergillus niger were capabled of producing enzymes at a faster rate to decompose the substrate hydrocarbon and released more CO2 and hence these potential fungi can be utilized effectively as agents of biodegradation in waste recycling process and Bioremediation of oil contaminated sites.